Direct Marketing In UK Retailing: Rhetoric And Reality - Reynolds, J; Shields, G (Elsevier, 1996)
In recent years a number of commentators, taking note of facilitating developments in customer information systems, have predicted a movement toward retail direct marketing in the UK. Speculation in the trade press as to the potential consequences of such a movement has become almost commonplace. The fact remains, however, that little is actually known about the extent to which retailers are even interested in, let alone practicing, direct marketing. Consequently, this study aims to provide an initial benchmark against which future retail direct marketing developments can be gauged. In summary, it appears to justify interest in the emergence of a retail direct marketing movement. The results show both a high level of interest in direct marketing media, and the potential for the adoption over time of more sophisticated direct marketing applications. However, there appear to be a number of barriers to the adoption and implementation of direct marketing in the retail business. These are identified and discussed.